PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PENGUNJUNG WISATA VANAPRASTHA GEDONG SONGO PARK KABUPATEN SEMARANG - Fatini, Nada Amirotul; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2020)
Tourism is one of the potential business sectors because the community's need to travel continues to increase. One of the natural attractions that are currently developing is Vanaprastha Gedong Songo Park which is a natural forest of pine belonging to the Perhutani Public Corporation and opened since 2010. The purpose of this research is to examined the effect of product quality and service quality on visitor satisfaction. The research used quantitative with explanatory research type and using a questionnaire as a data collection method. The sampling technique used non-probability sampling. The sample is 100 Vanaprastha tourists with certain predetermined criteria. Data analysis using Partial Least Square, with the SmartPLS 3.0 application.The results of the study are in line with the Theory of Consumer Behavior, especially in the scope of nature tourism. The analysis showed that product quality and service quality had a positive and significant effect on visitor satisfaction. The results showed that the quality of Vanaprastha tourism products is very attractive because it has beautiful natural scenery. As for service quality, the service of Vanaprastha tourism officers is considered to be very communicative and responsive. The limitation is the data collection is done when visitors are on tour so that the respondent might answer the question not seriously and carefully, and the respondent might not be familiar with the questions asked. The suggestion given to the manager is to pay more attention to the condition of the road to Vanaprastha, the availability of the number of gazebos, and the availability of a guide. For further research is to develop this research with different variables such as promotion, price, and destination image with a broader scope of research objects such as the entire Gedong Songo Temple tour.